Graphene: Controlled Growth of Single‐Crystal Twelve‐Pointed Graphene Grains on a Liquid Cu Surface (Adv. Mater. 37/2014). (October 2014) - Geng, Dechao; Meng, Lan; Chen, Bingyan; Gao, Enlai; Yan, Wei; Yan, Hui; Luo, Birong; Xu, Jie; Wang, Huaping; Mao, Zupan; Xu, Zhiping; He, Lin; et al.
<x xml:space="preserve">Abstract</x> Twelve‐pointed graphene grains are controllably fabricated on a liquid Cu surface by ambient pressure chemical vapor deposition, as described by G. Yu and co‐workers on page 6423. These novel‐shaped grains are characterized as single‐layer and single‐crystalline. The distinct nature of the alternating edge types (zigzag and armchair edges in sequence) in such a grain may result in their promising application in spintronics and other areas. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>